Social gradients in oral and general health among adolescents in Northern Norway. A cross-sectional and longitudinal cohort study. - Stangvaltaite, Lina (UiT Norges arktiske universitet, 2018)
[Oppgaven fjernet fra Munin etter epost fra forfatter. Legges ut igjen juni 2022. 02.06.2020 LL] Aim: To explore the social gradients in self-perceived oral and general health, caries experience and body mass index (BMI) in a Norwegian adolescent population. Methods: The data was retrieved from a population-based cohort study Fit Futures, which included all first-year high-school students aged 15-19 years, in two municipalities in Troms County, Northern Norway, in 2010-2011 (not including the summer months). Over 90% of the invited participants attended. All the data, except caries experience, BMI and 25(OH)D serum, was collected through the questionnaire. Analyzed sample consisted of 384 girls and 324 boys, with a participation rate of 63%. Multivariable binary logistic regression analysis stratified by gender was used to investigate the association between socioeconomic position indicators (mother’s education, parents’ employment and child’s school program) and outcomes. All models were adjusted for age, country of birth, household with adults, and a combined health variable, which included history of chronic diseases, alcohol consumption, smoking, use of snuff, physical activity, sugar and other unhealthy diet, vitamin D level, oral hygiene, self-esteem, mental health and sleep. Results: Girls attending vocational school program (vs program for specialization in general studies) had more than two times higher odds for being overweight/obese (OR 2.27, 95%CI 1.05-4.91) and for having higher than average DMFT score (OR 2.54, 95%CI 1.30-4.97). Moreover, these girls had more than two and a half times higher odds to perceive their general and oral health at baseline as less good (OR 2.79, 95% CI 1.27-6.12, and OR 2.54, 95%CI 1.30-4.96, respectively). Comparing to boys who attended the program for specialization in general studies, boys in vocational school program had more than three times higher odds to perceive their oral health at baseline as less good (OR 3.39, 95%CI 1.54-7.46), while boys in sports and ...